Antibiotic-Resistant Gram Negative Bacilli in Meals Delivered at a General Hospital, Italy. (9th September 2009) - Plano, Maria Rosa Anna; Di Noto, Anna Maria; Firenze, Alberto; Sciortino, Sonia; Mammina, Caterina
Abstract : This study aimed at detecting the presence of antibiotic-resistant Gram-negatives in samples of meals delivered at the University General Hospital of Palermo, Italy. Antibiotic resistant Gram negatives were isolated in July—September 2007 ffrom cold dishes and food contact surfaces and utensils. Bacterial strains were submitted to susceptibility test and subtyped by random amplification of polymorphic DNA (RAPD). Forty-six of 55 (83.6%) food samples and 14 of 17 (82.3%) environmental swabs were culture positive for Gram negative bacilli resistant to at least one group of antibacterial drugs. A total of 134 antibiotic resistant strains, 51 fermenters and 83 non-fermenters, were recovered. Fermenters and non-fermenters showed frequencies as high as 97.8% of resistance to two or more groups of antibiotics and non fermenters were 28.9% resistant to more than three groups. Molecular typing detected 34 different profiles among the fermenters and 68 among the non-fermenters. Antibiotic resistance was very common among both fermenters and non-fermenters. However, the wide heterogeneity of RAPD patterns seems to support a prominent role of cross-contamination rather than a clonal expansion of a few resistant isolates. A contribution of commensal Gram negatives colonizing foods to a common bacterial resistance pool should not been overlooked.